Criticism and Analysis of the Book Structuralism and Post-Structuralism, a Philosophical Approach - Mostafa Dashti Ahangar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Structuralism and poststructuralism are two of the most important and influential approaches in the humanities of the 20th century. These two approaches are raised in response to the special situation in philosophy and humanities, so they have to be paid attention to. The main question of this article is to survey of benefits and weaknesses in this book by the critical, descriptive method. It should be noted that this study was conducted in accordance with structuralist and poststructuralist theories, and this book has been studied in three phases: Methodological, formal, and content review phase. The books in this field, usually, are translated into the Persian language, but this book is an essay, so the purpose of this article is to review this book as an essay book. The most important value of this book is the novelty of the subject. Also, this book has its drawbacks of writing issues and punctuation. Great emphasis on philosophical issues, the extension of the opinion of structuralists and poststructuralists in different contexts of humanities, failure to the presentation of historical philosophy content properly, redundant repetition and inconsistency, are the other flaws in the book include.